Hemodiafiltration beyond the CONVINCE trial - Strippoli G. F. M.; Cromm K.; Pezoulas V. C.; Tachos N.; Fotiadis D.; Jaure A.; Malyszko J.; Anger M.; Fischer F.; Hegbrant J.; et al. (My University, 2026)
Online hemodiafiltration (HDF) is a dialysis modality that can improve patient outcomes beyond those achieved with conventional high-flux hemodialysis (HD) in patients with kidney failure. The CONVINCE trial, the latest and the largest of a series of randomized trials comparing HDF with HD, demonstrated a 23% reduction in the risk of all-cause mortality with high-volume HDF compared to high-flux HD. Systematic reviews of the totality of evidence confirmed cardiovascular and survival benefits of HDF. Further hard-endpoint trials are unlikely to change these findings. The challenge is implementation of these findings in clinical care. Nephrology is used to timeframes of 10-15 years before innovation gets implemented at the bedside, and this may well apply to HDF, particularly in regions where structural, regulatory, and financial barriers persist. In this narrative review, we discuss in broad terms the key items of a forward-looking research agenda for HDF after CONVINCE. Key priorities include real-world implementation studies; a strong focus on patient-reported outcomes; mechanistic research to understand why HDF is superior to HD and exploring personalized HDF regimens. Attaining these priorities will require leveraging innovative methods and we discuss two, target trial emulation methods and use of digital twin technologies. We aim to stimulate reflection and enthusiasm toward a modern approach to dialysis research that embraces innovation and centers on patient priorities. We advocate for world-class clinical guidelines on HDF, avoidance of opinion and position statements and a decisive, creative, and innovative research path. Patients with kidney failure deserve care informed by the best available evidence, implemented through rigorous guideline processes and adapted to patient preferences, health-system context, and feasibility.
Keywords: Tıp; Dahili Tıp Bilimleri; İç Hastalıkları; Nefroloji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Internal Diseases; Nephrology; Health Sciences; Üroloji ve Nefroloji; Klinik Tıp; Klinik Tıp (Med); Urology & Nephrology; Clinical Medicine; Clinical Medicine (Med); Üroloji; Urology